Sympathetic Overactivation in Patients With Essential Hypertension and Hepatic Iron Overload. Issue 5 (November 2020) - Seravalle, Gino; Dell'Oro, Raffaella; Quarti-Trevano, Fosca; Spaziani, Domenico; Bertoli, Silvio; Airoldi, Flavio; Mancia, Giuseppe; Grassi, Guido
Abstract : Iron overload has been recently shown to be associated with a hyperadrenergic state in genetic hemochromatosis. Whether this is also the case in essential hypertension, characterized by sympathetic activation and frequently by body iron overload, is unknown. In 17 healthy normotensive controls (age 52.3±3.2 years, mean±SE), in 21 age-matched patients with hypertension with iron overload (HT+), defined by serum ferritin levels, and in 28 hypertensives without this condition, we measured efferent postganglionic muscle sympathetic nerve traffic (microneurography), heart rate and blood pressure variability (power spectral analysis), serum ferritin, and metabolic variables. Muscle sympathetic nerve traffic was significantly ( P <0.02 at least) greater in HT+ than in patients with hypertension without iron overload and normotensive subjects both when expressed as bursts incidence over time (41.8±1.4 versus 31.5±1.4 and 23.6±0.9 bursts/min) and as bursts corrected for heart rate (55.3±1.8 versus 42.3±1.2 and 31.7±1.2 bursts/100 heartbeats). In HT+, low-frequency systolic blood pressure variability was significantly reduced. In HT+, but not in the other 2 groups, muscle sympathetic nerve traffic was significantly related to serum ferritin ( r =0.51, P <0.03), transferrin saturation ( r =0.47, P <0.03), and hepatic iron load ( r =0.76, P <0.0001, magnetic resonance imaging), as well as to homeostatic model assessment index values ( r =0.46, P <0.05). These data provide the first evidence that in HT+ elevated serum ferritin is associated with a hyperadrenergic state of greater magnitude than the one seen in patients with hypertension without iron overload. They also show that the potentiation of the sympathetic activation detected in HT+ is related to elevated serum ferritin and to the associated metabolic alterations, possibly participating in the increased cardiovascular risk characterizing iron overload.